Analisis Pemasaran Ikan Laut dalam Meningkatkan Pendapatan Nelayan di Kabupaten Sumba Barat Daya - Karolus Wulla Rato; Erniati Bili; Apliana Kaka; Cristian Hartanto Solo; Firgulius Bili (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to analyze marine fish marketing strategies that can increase fishermen's income in Southwest Sumba Regency. The fisheries sector is one of the main sources of income for local communities, but the challenges of marketing fish products faced by fishermen often hinder the improvement of welfare. The method used in this study is a qualitative approach with in-depth interview techniques and direct observation in the field. The results of the study indicate that the marine fish marketing system in Southwest Sumba is still relatively simple, with the role of middlemen dominating the distribution channels. This causes the selling price of fish to be suboptimal and reduces fishermen's income. Recommended marketing strategies include introducing direct marketing techniques, improving the quality of fish products through processing technology, and building stronger partnerships between fishermen and the market. This study also found that the existence of fishermen's cooperatives can be an alternative to improving marketing access and increasing fishermen's bargaining power. With the implementation of a more efficient marketing strategy, it is hoped that fishermen's income in Southwest Sumba Regency can increase significantly.